2020
DOI: 10.3389/fbioe.2020.00694
|View full text |Cite
|
Sign up to set email alerts
|

Functional Validation of Two Fungal Subfamilies in Carbohydrate Esterase Family 1 by Biochemical Characterization of Esterases From Uncharacterized Branches

Abstract: The fungal members of Carbohydrate Esterase family 1 (CE1) from the CAZy database include both acetyl xylan esterases (AXEs) and feruloyl esterases (FAEs). AXEs and FAEs are essential auxiliary enzymes to unlock the full potential of feedstock. They are being used in many biotechnology applications including food and feed, pulp and paper, and biomass valorization. AXEs catalyze the hydrolysis of acetyl group from xylan, while FAEs release ferulic and other hydroxycinnamic acids from xylan and pectin. Previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 55 publications
(87 reference statements)
1
19
0
Order By: Relevance
“…The protein sequences of the detected proteins were shared between 82 and 90% identity between each other. According to the CAZy classification system, the CE1 family contain most of the characterized fungal acetyl xylan esterases, feruloyl esterases and p -coumaroyl esterases [ 53 , 71 ]. These enzymes are involved in breaking down ester cross-links of lignin and hemicelluloses and in lignin solubilization [ 72 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…The protein sequences of the detected proteins were shared between 82 and 90% identity between each other. According to the CAZy classification system, the CE1 family contain most of the characterized fungal acetyl xylan esterases, feruloyl esterases and p -coumaroyl esterases [ 53 , 71 ]. These enzymes are involved in breaking down ester cross-links of lignin and hemicelluloses and in lignin solubilization [ 72 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…The plasmids pPicZαA- xegA Ds and pPicZαA- xegA Po were extracted and linearized with PmeI (New England Biolabs, Ipswich, MA) and subsequently transformed into P. pastoris strain X-33 by electroporation. The positive colonies were selected by colony Western Blot using 6x-His Tag Monoclonal Antibody conjugated to alkaline phosphatase (Invitrogen, Thermo Fisher Scientific, Carlsbad, CA, USA) and detected with a chromogenic substrate 5-bromo-4-chloro-3-indolyl phosphate/nitro blue tetrazolium (BCIP/NBT) ( Li et al., 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Cellulose, one of the major components of lignocellulose, is a homopolysaccharide with amorphous and crystalline regions [44] made of glucose monomers linked by β-1,4-Dglucan. Hemicellulose however is a heterogenous polysaccharide conformed by a xylan backbone that contains xylose, arabinose, mannose, glucose, galactose and sugar acids in different proportions depending on the source [43,45].…”
Section: Enzymes Targeting Lignocellulosic Polysaccharidesmentioning
confidence: 99%
“…Hemicellulolytic carbohydrate esterases remove the ester group from carbohydrates and facilitates the access to GHs [64]. Esterases are classified into 18 families according to the CAZy database (www.CAZy.org; accessed on 23 September 2021), these include feruloyl esterases (EC 3.1.1.73) from the CE1 family which catalyze the cleavage of the ester bond at the O-5 position between a ferulic acid and arabinose liberating hydroxycinnamic acids; as well as acetyl xylan esterases (EC 3.1.1.72), which in turn catalyzes the cleavage of ester linkages on the position O-2 and O-3 between an acetyl group and xylose [45,65]. Various studies reported higher expression of hemicellulases than cellulases, as hemicellulose is more exposed than cellulose [52,53].…”
Section: Enzymes Targeting Lignocellulosic Polysaccharidesmentioning
confidence: 99%